2000
DOI: 10.1046/j.1365-2915.2000.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

An epizootic of patent iridescent virus disease in multiple species of blackflies in Chiapas, Mexico

Abstract: Simulium blackfly larvae (Diptera: Simuliidae) were collected from rivers and streams at 500-1500 m a.s.l. in Chiapas State of southern Mexico. Among 45 sites surveyed over an area of 2300 km2 (around 15 degrees 15'N 92 degrees 20'W), some Simulium larvae from three sites were opalescent violet-blue, interpreted as patent infection with invertebrate iridescent virus (IIV). Dissection confirmed the presence of putative Iridovirus particles, 130nm diameter, but no IIV isolates were obtained from homogenates inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The incidence of patent disease in host populations is typically very low, although occasional epizootics have been observed in lepidopteran species (Sikorowski and Tyson 1984;Sieburth and Carner 1987), crickets (Fowler 1989), craneflies (Ricou 1975), mosquitoes (Fedorova 1986), and blackfly larvae (Hernández et al 2000). Studies on blackflies and Lepidoptera have indicated that there exists considerable genotypic variation in IIV populations; individual insects collected at the same place and time differed in their respective RFLP profiles and in the size of the restriction fragments that hybridized to an MCP gene probe in Southern blots (Williams and Cory 1994;Williams, unpublished data).…”
Section: Ecologymentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of patent disease in host populations is typically very low, although occasional epizootics have been observed in lepidopteran species (Sikorowski and Tyson 1984;Sieburth and Carner 1987), crickets (Fowler 1989), craneflies (Ricou 1975), mosquitoes (Fedorova 1986), and blackfly larvae (Hernández et al 2000). Studies on blackflies and Lepidoptera have indicated that there exists considerable genotypic variation in IIV populations; individual insects collected at the same place and time differed in their respective RFLP profiles and in the size of the restriction fragments that hybridized to an MCP gene probe in Southern blots (Williams and Cory 1994;Williams, unpublished data).…”
Section: Ecologymentioning
confidence: 99%
“…There is clear evidence of seasonality in the prevalence of IIV infections that correlates with fluctuations in precipitation and soil humidity and/or host densities (Ricou 1975;Grosholz 1993;Hernández et al 2000). The persistence of IIV-6 in soil depends very much on moisture content (Reyes et al 2004) and the presence of clay and iron minerals (Christian et al 2006).…”
Section: Ecologymentioning
confidence: 99%
“…They infect typically invertebrates in humid or aquatic habitats, but their ecology is poorly understood, probably because the incidence of overt infection is extremely low (Williams 1998). Epizootics have been reported at sites of high host density, for example rivers and streams containing high densities of Simulium blackfly larvae (Hernandez, Maldonado & Williams 2000). However, a large proportion of a population from the River Ystwyth, Wales, was found to harbour a covert infection.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys of patent infection in blackfly species (Diptera: Simuliidae) have typically observed less than 10% of individuals infected (based on cadaver opalescence) (Weiser 1968; Batson et al 1976; Takaoka 1980; Avery and Bauer 1984; Batson 1986; Erlandson and Mason 1990; Williams and Cory 1993). The use of sensitive bioassays for invertebrate iridescent virus (IIV) infection, including PCR and DNA-DNA hybridization, reveal that a large number of individuals in a population may have covert, non-lethal infections (Ward and Kalmakoff 1991; Williams 1993, 1995; 1996; Marina et al 1999; Hernandez et al 2000). The invertebrate iridescent virus 6 (IIV6), synonymous with Chilo iridescent virus (CIV) ( Iridoviridae: Iridovirus ), has an icosahedral symmetry with a particle diameter of 120–130nm containing a single copy linear dsDNA genome 212 kbp in length (Jakob et al 2001).…”
Section: Introductionmentioning
confidence: 99%